14. STRESS AND SOME INFLUENCING FACTORS AMONG NURSING STUDENTS AT DA NANG UNIVERSITY OF MEDICAL TECHNOLOGY AND PHARMACY (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the rate of stress level of nursing students at Da Nang University of Medical Technology and Pharmacy and some influencing factors.Method: Cross-sectional study on 510 nursing students at Da Nang University of Medical Technology and Pharmacy. Stress assessment using DASS-21 scale.Results: The rate of stress in students is 53.1%. Of which, mild, moderate, severe, and very severe stress are respectively at the rate of: 18.4%, 18.8%, 11.6%, 4.3%. Influencing factors to stress include: living conditions, perceived health status, frequency of exercise, parents' marriage, and satisfaction with the major (p
Keywords: DASS – 21; nursing students; stress.